2021
DOI: 10.1002/mus.27378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on the quality of life of patients with neuromuscular disorders in the Lombardy area, Italy

Abstract: Introduction:/Aims: Patients with neuromuscular disorders (NMDs), including many elderly, immunosuppressed, and disabled individuals, may have been particularly affected during the coronavirus disease 2019 (COVID-19) pandemic in Lombardy, a COVID-19 high-incidence area between February and May 2020. We aimed to evaluate the effects of the COVID-19 pandemic on the quality of life (QoL) and perceived disease burden of this group of patients.Methods: We conducted a cross-sectional phone-based survey study between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Moreover, rehabilitation services and outpatient visits were the most affected, having been suspended in 93% of the centres. In another study by Gagliardi et al evaluating the effects of the COVID-19 pandemic on the quality of life of 205 patients with NMD in the Lombardy area of Italy, 27 the authors reported that outpatient visits were postponed in 57.1% of cases and that 50.7% of patients experienced a cancellation of scheduled diagnostic tests, suggesting that the pandemic substantially disrupted clinical and support services for patients with NMDs and reduced quality of life. Taken together, the results from these two European studies suggest that the impact of the COVID-19 pandemic on patients with NMDs was higher in Europe than in Japan; however, the reasons for the higher impact are currently unclear and must be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rehabilitation services and outpatient visits were the most affected, having been suspended in 93% of the centres. In another study by Gagliardi et al evaluating the effects of the COVID-19 pandemic on the quality of life of 205 patients with NMD in the Lombardy area of Italy, 27 the authors reported that outpatient visits were postponed in 57.1% of cases and that 50.7% of patients experienced a cancellation of scheduled diagnostic tests, suggesting that the pandemic substantially disrupted clinical and support services for patients with NMDs and reduced quality of life. Taken together, the results from these two European studies suggest that the impact of the COVID-19 pandemic on patients with NMDs was higher in Europe than in Japan; however, the reasons for the higher impact are currently unclear and must be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…At the time, the study was initiated in March 2020, it was unknown what the impact of COVID-19, and the restrictions on FSHD patients would be. In Italy, research on various Neuromuscular Disorders (NMDs) has shown a subjective worsening of the NMD symptoms and a significant worsening of quality of life (QoL) during the pandemic [ 8 , 9 ]. It is expected that the worsening of disease aspects and QoL will also have occurred in FSHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic and associated control measures have had a big, though variable, impact on the general populations’ health, including their mental health [ 27 ]. It has been shown that in patients with NMDs, including a few patients with Pompe disease, the pandemic resulted in worsening of the quality of life, worsening of their underlying disorder and in some cases in fear and anxiety [ 28 31 ]. The COVID-19 pandemic has also been challenging for the disease-specific treatment of NMDs such as ERT, physical therapy and respiratory therapy [ 28 , 29 , 32 35 ].…”
Section: Introductionmentioning
confidence: 99%